Analis Perancangan Dan Penerapan Keamanan Jaringan Menggunakan Metode Intrusion Detection System (IDS), Intrusion Prevention System (IPS) Dan Demilitarized Zone (DMZ) Pada PT. Maha Digital Indonesia (Mahapay) - Trijanitra, Evan; Arya Adhyaksa Waskita; Taswanda Taryo (Jurnal Ilmu Komputer, 2024)
Network security systems, in recent years have become the main focus in the world of securing other important data, this is due to the high number of suspicious threats (Suspicious Threats) and attacks from the Internet. Network security involves efforts to protect data and computer systems from detrimental threats, such as cyberattacks, malware, and data theft. The existence of increasingly complex and evolving threats has increased awareness of the need for strong network security. PT. Maha Digital Indonesia (Mahapay) is a company operating in the field of EDC Field Service where it is very important that client data is kept confidential. This requires good network security to maintain the confidentiality of the data. So the aim of this research is to implement network security using the Intrusion Detection System (IDS), Intrusion Prevention System (IPS) and Demilitarized Zone (DMZ) methods as network security at PT . Maha Digital Indonesia (Mahapay). The results of this research are the formation of connections between networks in the topology along with the successful functioning of the Intrusion Detection System (IDS) and Intrusion Prevention System (IPS) detecting and preventing suspicious activities carried out by attackers and the operation of rules for the DMZ area. Success in the application is tested again by carrying out several attack methods that will be analyzed such as Syn Flood Attack, Ping Of Death and Port Scanning which will be handled by the configuration that has been applied to the network and server.